Social, Material and Political Constructs of Arctic Childhoods An Everyday Life Perspective - Rautio, Pauliina; Stenvall, Elina (Children: Global Posthumanist Perspectives and Materialist Theories, 2019)
This book addresses the geopolitical notion of the 'Arctic' through the everyday experiences of children. It explores the Arctic as various materializations that matter to, condition and define childhoods in Nordic countries. Presenting nine thematically very different but theoretically and methodologically coherent studies, it enables readers to gain an in-depth understanding of a selection of recent sociomaterialist, posthumanist and post-anthropocentric research on childhood in the Nordic context. The book offers new ideas and insights as to what matters in children's lives - in Arctic contexts.